Linguagem teatral e educação: um elo possível - Santana, Suzimar Barbosa (2010)
The crisis in contemporary education demonstrates the need to think applicable alternatives, approximating school and life and making it, for that reason, more attractive. The current context requires from school a profile of students and teachers capable of creating a favorable environment of developing multiple intelligences and of waking up latent potentialities. The present work has as main objective to contribute for a thinking regarding the importance of the use of theatrical language in educational activities, as well as to make available the results for a reflection on the benefits that the theater can promote in children's and young s integral development. For the development of that work, we chose observations of the developed activities and the analysis of reports of theatrical experiences accomplished at Colégio Santo Antônio de Jesus, in kindergarten classes of 2010, besides the bibliographica research. For this, phenomenological methods were used, which consists of describing the experience just as it is, and the observational method, which consists of observing and registering relevant events related to the research theme. The result of that work can be used by students and theater professionals, educators that are interested in the theme and schools that want to accomplish a differentiated work, pepping the school space with the active participation of the students, the family and the community, which will feel part of such complicated process that is educating. Therefore, that work provides discussions regarding the possibility of creating a bond between theater and education, and certainly it will serve as incentive so that educators can incorporate in their annual plans such activities, helping in the formation of active happy children, which will be capable of participating as main actors in that great show, that is the life.